Detecting malicious nodes using data aggregation protocols in wireless sensor networks - Balamurugan, P.; Devi, M. Shyamala; Sharmila, V. (International Journal of Engineering and Technology, 2017)
At present scenario, sensor devices are used in various fields for gathering information so all those data should be secured safely. Securing data is an important role in Wireless Sensor Networks (WSN). WSN is extremely essential for the purpose of reducing the complete redundancy and energy consumption during gathering data among sensor nodes. Optimized data aggregation is needed at cluster head and Base Station (BS) for secured data transmission. Data aggregation is performed in all routers while forwarding data from source to destination node. The complete life time of sensor networks is reducing because of using energy inefficient nodes for the purpose of aggregation. So this paper introduces the optimized methods for securing data (OMSD) which is trust based weights and also completely about the attacks and some methods for secured data transmission.Â